2002
DOI: 10.1086/339448
|View full text |Cite
|
Sign up to set email alerts
|

Increased Survival of Persons with Tuberculosis and Human Immunodeficiency Virus Infection, 1991–2000

Abstract: To determine factors associated with the occurrence of human immunodeficiency virus (HIV) infection and tuberculosis (TB) disease (HIV-TB) and the associated survival rate, we analyzed patients with HIV-TB at Grady Memorial Hospital, Atlanta, Georgia, from 1991 through 2000. Overall, 644 patients with HIV-TB were seen. The number of HIV-TB cases per year was highest in 1992 (102 cases) and declined to 39 cases in 2000. Over time, patients were more likely to be enrolled in the HIV outpatient clinic (P<.01), bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 19 publications
(15 reference statements)
0
20
0
2
Order By: Relevance
“…17,18 In the absence of US autopsy studies, one US study using smears at death and tissue cultures found that 22% of a 1997 TB-HIV cohort died, 44% of which were from TB. 7 A random sample (n = 20) record review of the cause of TBassociated deaths during 2000-2004 in California found that 85% (n = 17) were definitely or possibly TB-related and that 60% (n = 12) could have been prevented; death certificate data were often inaccurate in determining the cause of death. 19 Reviews of medical records and other data, in the absence of autopsies, could improve the determination of the cause of TBassociated mortalities, 19 and improve the completeness of data on excess alcohol use, injecting drug use, non-injecting drug use, homelessness, and residence in a long-term care facility or correctional facility.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 In the absence of US autopsy studies, one US study using smears at death and tissue cultures found that 22% of a 1997 TB-HIV cohort died, 44% of which were from TB. 7 A random sample (n = 20) record review of the cause of TBassociated deaths during 2000-2004 in California found that 85% (n = 17) were definitely or possibly TB-related and that 60% (n = 12) could have been prevented; death certificate data were often inaccurate in determining the cause of death. 19 Reviews of medical records and other data, in the absence of autopsies, could improve the determination of the cause of TBassociated mortalities, 19 and improve the completeness of data on excess alcohol use, injecting drug use, non-injecting drug use, homelessness, and residence in a long-term care facility or correctional facility.…”
Section: Limitationsmentioning
confidence: 99%
“…2 Several studies document that HIV-infected TB patients on antiretroviral therapy (ART) during TB therapy survive for longer than those not on ART. [3][4][5][6][7] The present study describes trends in mortality and characteristics associated with TB diagnosis at death or death during TB therapy. We also describe diagnostic procedures for patients diagnosed at death to assess missed opportunities for prevention.…”
mentioning
confidence: 99%
“…Conversely, the diagnosis of TB can lead to life-saving HIV=AIDS care. 13,[18][19][20] However, many persons with TB=HIV have advanced HIV disease at the time of TB presentation, and frequently are either unaware of their HIV status, or are not receiving HIV care. 19,21 TB=HIV coinfected patients in North America are also more likely to have social problems complicating care, including homelessness, illicit drug use, unemployment, or incarceration, which may further complicate their ability to access HIV-specific care.…”
Section: Introductionmentioning
confidence: 99%
“…13,[18][19][20] However, many persons with TB=HIV have advanced HIV disease at the time of TB presentation, and frequently are either unaware of their HIV status, or are not receiving HIV care. 19,21 TB=HIV coinfected patients in North America are also more likely to have social problems complicating care, including homelessness, illicit drug use, unemployment, or incarceration, which may further complicate their ability to access HIV-specific care. 13 Patients with TB in North Carolina are almost exclusively managed through the public health system, so understanding the barriers to care and outcomes in coinfected patients is vital to improving the quality of care in our state, and relevant to other large public health programs in other areas.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing linkage of TB with the human immunodeficiency virus (HIV) pandemic has magnified this tragedy in the past decade. The World Health Organization estimates that at least six million people worldwide are coinfected with M. tuberculosis and HIV (18). The HIV-M. tuberculosis coinfection rates exceed 5% in eight African countries, and in South Africa alone two million adults are coinfected (9).…”
mentioning
confidence: 99%